The Establishment of İzziye Distriet and Its Plaee in Turkish National Struggle - Öztürk, Mustafa (Ankara Üniversitesi, 2005)
bı the Ottoman administratimlal organization nomadic tribes were divided as administrative uııits in statutes of Nahiya and Qada. So they could be colltroled by the perspectives of administrative, economic, militarial and security . For exanıple, Aleppo Turkoman Qada, Turkan and Abu Tahir Nahiyas were so. In 16th century, Kilis as the centre of Akriid Tribes which were spreaded to Aleppo, Birejik, Urfa, Samsad, Kahta, Gerger, Hısn-ı Mansur (Adıyaman) and Amik, were divided as İzzeddinlü or Akriid Qada. All these religious communities which had spreaded to the area were known as İzzeddinlü Taifesi. And also İzzeddin Bag was Mir-i Akriid. This traditian continued until 19th century. At second half of 19th century it become nesesary to settle the tribes and in 1865 İzziye Qada was founded near Islahiye and Hassa Qadas with the attempts Firqa-i Islahiya. Also the religional communities Oqju İzzeddinli Amiki and Sheyhler Tribes in the qada which had Juqanlı and Sapqanlı villages as the centre were made nahiyas. İzziye, which was stili Qada until 1895, was linked Kilis at the same year. Being on the significant location on the road of Aleppo-Marash İzziye Qada after the Moundros Pact, during the marshing of French ahead to Anatolia on February 1919, they started the first struggles agai nst the French and unti i the autumn of 1920, they were really presented their beneficial services. But, with Ankara Pact, wiclı was singed on October J 6, 1921, some villages of İzziye were lefi in Syria, which was lUıder French Mandare. At the boundary events in 1938, Oqju İzzeddinli Tribe weakened the autllOrity of French over the area. It is dean that. these developments were important factors in the solutiOlIS of Hatay Question

Osmanlı idari teşkilatında konar-göçer aşiretler na/liye veya kaza statüsünde birer idari birim olarak taksim edilmişlerdir. Bu suretle onlarm idari, malf, askerf ve güvenlik bakımından kontrol edilmeleri sağlanmış oluyordu. Mesela; Halep Türkmen Kazası, Türkan, Ebu Tahir na/liyeleri bu cümledendir. /6. Yüzyılda Kilis merkez olmak üzere, Halep, Birecik, Urfa, Samsat, Kahta, Gerger, Hısn-ı Mansur (Adıyaman) ve Amik Ovalarına yayılmış bulunan Ekrad cemaatleri de İzzeddinlü veya Ekrad Kazası olarak taksim edilmiştir. Bütün bu bölgeye yayılan cemaatler İzzeddinlü Taifesi olarak biliniyordu ve İzzeddin Bey de Mfr-i Ekrad idi. Bu gelenek 19. yüzyıla kadar devam etti. /9. yüzyılm ikinci yarısında aşiretlerin iskanı kaçınılmaz hale gelmiş ve 1865 yılında Fırka-i İslahiye çalışmaları çerçevesinde İslahiye ve Hassa kazalarıyla birlikte İzziye Kazası da kurulmuştur. Merkezi Cukanlı ve Sapkanlı köyleri olan Kazanın Okçu İzzeddinli, Amikf ve Şeyhler cemaatleri de Nahiye haline getirilmiştir. /895 yılına kadar kaza olarak kalan İzziye, bu tarihte Kilis'e bağlanmıştır. İzziye Kazası, Halep-Maraş yolunun önemli bir mevkiinde olması dolayısıyla, Mondros Mütarekesinden sonra Fransızlarm Anadolu 'ya ilerlemeleri sırasında, Şubat 1919'da Fransızlara karşı ilk mücadeleleri başlatmışlar ve 1920 yılının sonba/tarına kadar büyük yararlıklar göstermişlerdir. Ancak 16 Ekim 1921 Ankara Antlaşmasıyla İzziye kazasının bazı köyleri Fransız mandası altındaki Suriye'de kalmıştır. /938 tarihindeki sıııır olaylarında Okçu İzzeddinli cemaati Fransızların bölgedeki otoritesini hayli zayıjlatmıştır. Bu gelişmelerin Hatay Meselesinin çözümünde önemli bir etken olduğu aşikardır.
İzziye Kazasının Kuruluşu ve Milli Mücadeledeki Yeri ----The Establishment of İzziye District and Its Place in Turkish National Struggle
Keywords: Archaeology; Arkeoloji